Mental and Emotional Preparation of Early Childhood in Transition to Primary School - Wahyuni, Sri (Bidayatuna, 2024)
This study explores the role of Early Childhood Education (PAUD) teachers in mentally and emotionally preparing children for the transition to elementary school. With a qualitative approach and case study design, the study identifies various challenges that children face, including anxiety, lack of confidence, and difficulty adapting, which can arise from a lack of adequate preparation. The findings suggest that inadequacy in preparation can degrade a child's social status and trigger behaviors of helplessness and cunning. Therefore, educators and parents must provide appropriate support to help children navigate this transition better. This research is expected to provide insights for developing more effective policies and practices supporting early childhood readiness in the new school environment.